The effects of work life quality, organizational support, and organizational justice on intent to stay with the organization, with job satisfaction as a mediating variable - Suhendro Suhendro; Anita Maharani; Ake Wihadanto (Insight Management Journal, 2026)
This study aims to analyze the effect of Quality of Work Life (QWL), Perceived Organizational Support (POS), and Organizational Justice (OJ) on Intention to Stay (IS) with Job Satisfaction (JS) as a mediating variable among casual daily workers at the Center for Teaching Materials (PLBA), Open University. The research method used a quantitative approach with an explanatory research design. The sample consisted of 121 respondents selected through simple random sampling technique. Data analysis employed SEM-PLS with SmartPLS 3.0. The results showed: (1) QWL and OJ had a positive and significant effect on JS, while POS had no significant effect; (2) JS had a positive and significant effect on IS and was the strongest predictor; (3) Not all exogenous variables had a direct effect on IS; (4) JS acted as a full mediator in the relationship between OJ and IS. The adjusted R² value of 0.732 for IS indicates that the model has strong predictive ability. These findings confirm that job satisfaction is the key to increasing the intention to stay among casual daily workers. Practically, PLBA management needs to strengthen organizational justice, improve quality of work life, and build a culture of appreciation to foster job satisfaction and long-term loyalty.